All Things Thrown and Wonderful, All Memories Great and Small12. Issue 4 (17th September 2013) - Wilkinson, Alex
Abstract And the Lord God made them all. I went to Sunday school and like lots of other kids (though far from all) came to an age at which I simply stopped going. Nothing conscious about it, I don't think, it's just those sets of spaces stopped becoming; stopped like nothing physical can stop, like a car crashing into a wall and instead of rebounding being merely consumed in whole. I (re)member, in my naive teens (when is this? I do not know. Perhaps the time of the Iraq war, but maybe this was a different car journey) I once came out with the statement (which was not particularly naive especially) "I think God exists, how did we all get here otherwise". Me, my sister that is two years older than me, my mum and dad, were on the road from Auchmuir Bridge towards Stirling around Loch Leven, the loch in Fife, Scotland, on which Mary Queen of Scots was held on an island. I have an image of a memory of going there as well. It is thus, however, that I (re)member the initiation into a different vision of the universe and everything. Yet it is a state clearly pleated bewilderingly. As an event it exists in what Deleuze and Guattari term a "rhizome, a burrow", with "flights of escape" which have no beginnings or ends, mere initialities and finalities. 3This is strange. It is not a polemic, nor does it have an explicit argument, except perhaps to ask the question that always dances on a pinhead – as Bohumil Hrabal once put it, "Pirouettes on a Postage Stamp" 4 – is there any escape? I think I sang "All Things Bright and Beautiful" at my Gran's funeral, but it might have been something else. We stopped in the house of the priest and watched England lose the Cricket World Cup in 1999; they played in blue. That's how I (re)member the year of my Gran's funeral. The church I used to go to burned down. Arson, I think.